MARGARET’S EMOTIONAL AND SOCIAL LONELINESS IN TENNESSEE WILLIAM’S “A CAT ON THE HOT TIN ROOF” - Saddam Husien (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
This study concentrates to analyze Margaret’s character about loneliness that experience by her in Tennessee William’s a Cat on the Hot Tin Roof. Loneliness is unpleasant situation that experience by someone when the one’s desire or ambition is not equivalent in social relationship. Furthermore, the source of the data is telling about someone who experiences loneliness which contains the type of loneliness, effect of loneliness and the effort to overcome from loneliness, consequently the theory of loneliness is chosen. Besides that, this study is qualitative design because the data are collected in the form of words. The data of this study are narrator’s explanations and the character’s utterances related to the loneliness experienced by Margaret and the writer has function as the key instrument in this research. According to the analysis of the drama, the writer has finds the answer of the research problem, that are types and effect of Margaret’s loneliness and Margaret’s effort to overcome or coping loneliness in Tennessee William a Cat on the Hot Tin Roof. There are two types of Margaret’s loneliness, they are emotional and social loneliness. Firstly, Margaret’s emotional loneliness is her unsatisfactory relation with Brick. She does not get intimate relation from Brick. Therefore, she cannot get unpleasant situation from Brick. Secondly, Margaret’s social loneliness, she as a part of Brick’s family is not respected and accepted in the family due to her childless and Brick’s addiction to liquor. Effects of Margaret’s loneliness. She transforms to be rude and frantic, she becomes talkative person, and the last effect is she has much power to be brave person. Margaret’s effort to overcome her loneliness, she tries to understand Brick’s situation and attitude to get attention and more communication with him.